Watchful waiting for small non-functional pancreatic neuroendocrine tumours: nationwide prospective cohort study (PANDORA). Issue 13 (30th March 2021) - Heidsma, C M; Engelsman, A F; van Dieren, S; Stommel, M W J; de Hingh, I; Vriens, M; Hol, L; Festen, S; Mekenkamp, L; Hoogwater, F J H; Daams, F; Klümpen, H -J; et al.
Abstract : This prospective nationwide cohort study examined the feasibility of a watchful-waiting protocol for non-functional pancreatic neuroendocrine tumours (NF-pNET) of 2 cm or smaller. In total, 8 of 76 patients (11 per cent) with a NF-pNET no larger than 2 cm showed significant tumour progression (more than 0.5 cm/year) during 17 months of follow-up, of whom two opted for resection. No patient developed metastases. Quality of life was poorer than in the reference population. Watchful waiting seems a safe alternative to upfront surgery in patients with a NF-pNET no larger than 2 cm, although longer follow-up is necessary.